If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) = -1(x + 14) Reorder the terms: 5(2 + x) = -1(x + 14) (2 * 5 + x * 5) = -1(x + 14) (10 + 5x) = -1(x + 14) Reorder the terms: 10 + 5x = -1(14 + x) 10 + 5x = (14 * -1 + x * -1) 10 + 5x = (-14 + -1x) Solving 10 + 5x = -14 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 10 + 5x + x = -14 + -1x + x Combine like terms: 5x + x = 6x 10 + 6x = -14 + -1x + x Combine like terms: -1x + x = 0 10 + 6x = -14 + 0 10 + 6x = -14 Add '-10' to each side of the equation. 10 + -10 + 6x = -14 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = -14 + -10 6x = -14 + -10 Combine like terms: -14 + -10 = -24 6x = -24 Divide each side by '6'. x = -4 Simplifying x = -4
| 5-8x=50-43x | | (3)+(-7)+(11)=x | | 4u+5=-15 | | 0.4x+1.2=4.8 | | 0.3x+1.4(2x-5)=-22.5 | | .5+9x=1 | | 4x+1+5-2x+3=2x-5+x | | (-3)+(7)=x | | 11+6x=35 | | (-7)+(-3)=x | | x^2+2x+7=6x+3 | | (x-8)(5x+6)=(x-10)(x-2) | | 12=n/4+8 | | 9x+4=-6x+-17 | | (3-c^2d)(4-4c^2d)=0 | | y+5=0.5x | | -38=5v-3 | | x^2+4x-1=7x+9 | | 4x+13=93 | | 2y^2+y-15= | | 48-4x=7x+14 | | 0.20(y-8)+0.8y=0.02y-0.3 | | 2x-8=9x+6 | | 2(3x+8)-x=7x+4 | | 260=21-v | | 2y^2+11y+14= | | 2x-y=-10x+2y | | 5x+33=15x-62 | | 3x+27=8x-7 | | 5-(3d-4)=6 | | 3n/7-1=1/8 | | 3-8c=25 |